The Big-Fish-Little-Pond Effect on the Four Facets of Academic Self-Concept - Hoferichter, Frances; Lätsch, Alexander; Lazarides, Rebecca; Raufelder, Diana (Frontiers in Psychology, 2018)
The social context plays a decisive role in the formation of the academic self-concept (ASC) and has been widely studied as the Big-Fish-Little-Pond-Effect (BFLPE). This effect describes that comparable talented students in high-achieving school settings have a lower ASC compared to equally talented students attending low-achieving settings. Past research has focused on students’ domain-specific ASC, while little is known about the relation of achievement-related classroom compositions and the various facets of ASC. Additionally, BFLPE-research has been critiqued to build its theoretical frame on social comparison theory, without providing sufficient empirical support. To address this gap, we analyzed how the single student’s social, criterial, absolute, and individual ASC relate to class-level achievement of 8th graders. Applying Multilevel Structural Equation Modeling (MLSEM) we found that all facets of ASC were significantly related to average-class achievement, while student’s social ASC revealed the strongest associated. The results reveal explicitly that average-class achievement is strongly related to social comparison processes.